Characteristics and Flavonoid Content of Honey Apis dorsata Binghami from The Manembo Forest of South Minahasa - Melita Irene Gracia Kaligis; Yermia Semuel Mokosuli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
One of the producers of honey bees in North Sulawesi comes from the Manembo Forest, South Minahasa. Today many ordinary people do not know the quality of good honey. This study aims to study the characteristics of bee honey from the South Minahasa Manembo Forest based on SNI. The research was conducted in April-July 2022. The research method used for testing the quality of honey was using qualitative research methods. The data obtained were then analyzed using descriptive data analysis. Determination of total flavonoid levels using quercetin as a comparison. The absorbance value was measured by UV-Vis spectro-photometer. The absorbance value is then entered into the linear regression equation. The results showed that the characteristics of Manembo forest honey, South Minahasa Regency based on SNI 2018 parameters met the standards and quality with the percentage of reducing sugar 68.53%, sucrose content 3.07%, insoluble solids 0.14%, diastase enzyme DN=4 and 0.03% ash content while those that do not meet the standard are water content with a percentage of 25%. The results of the analysis of the total flavonoid content showed a value of 1.6 mgQE/g. For further research, it is recommended to make an antidiabetic or anti-bacterial analysis in forest honey.